CREATING WEALTH FROM GROUNDWATER FOR DOLLAR-A-DAY FARMERS: WHERE THE SILENT REVOLUTION AND THE FOUR REVOLUTIONS TO END RURAL POVERTY MEET - Polak P.; Yoder R. (My University, 2006)
More than 550 million of the current 1.1 billion people earning less than $1-a-day earn a living from agriculture in developing countries. A revolution in water control is needed to develop and mass-disseminate new, affordable, small-plot irrigation technologies. A revolution in agriculture is required to enable smallholders to produce high-value, marketable, labor-intensive cash crops. A revolution in markets is needed to open access to markets for the crops they produce and the inputs they need to produce them. Finally, a revolution in design, based on the ruthless pursuit of affordability, is needed to harness shallow groundwater. The experiences of suppliers of treadle pumps, low-cost drip irrigation and water storage systems were examined. The wealth these technologies generated, coupled with falling prices for small diesel pumps in countries like India and China, created a suitable environment for the rapid adoption of affordable diesel pump tubewells, which in turn created vigorous water markets and expanded access to affordable irrigation water for smallholders. The combination of smallholder-centered revolutions, along with the ‘silent revolution in groundwater’ described by Llamas and Martinez-Santos (Water Sci Technol 51(8):167–174, 2005) provide new practical options for meeting the UN Millennium Development Goals on poverty and hunger by 2015.
Keywords: IRRIGATED AGRICULTURE; TREADLE PUMPS; DRIP IRRIGATION; SMALLHOLDERS; WATER MARKETS